KEMAMPUAN FISIK DAN TINGKAT KETERAMPILAN DASAR BERMAIN SEPAK BOLA PADA SISWA PUTRA EKSTRAKURIKULER SEKOLAH DASAR DABIN 1 KECAMATAN RANDUBLATUNG KABUPATEN BLORA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the physical ability and the level of basic skills students playing football in elementary extracurricular son Dabin 1 Blora Randublatung the District in 2013.The population in this study were all students who were in elementary school extracurricular Dabin 1 Randublatung districts . In this study sample using purposive sampling of 50 students who take extracurricular activities at school . The method used in this study is a survey method tests . For various physical abilities tests used were : 50 -meter sprint , long jump without prefix , depending elbow bend , run back and forth 4 x 10 meters , lying sit 30 seconds , lentuk togok to face , and ran 600 meters away . As for the basic skills of playing soccer tests used were : passing and stopping , heading , dribbling , and shooting.Based on the survey results revealed that physical ability and level of basic skills students playing football in elementary extracurricular son Dabin 1 Subdistrict Randublatung Blora including medium category .